2006
DOI: 10.3818/jrp.8.2.2006.57
|View full text |Cite
|
Sign up to set email alerts
|

Who Returns to Prison? A Survival Analysis of Recidivism among Adult Offenders Released in Oklahoma, 1985 – 2004

Abstract: Identifying and evaluating the influence of factors that predict offenders' post-release performance is central to the study of recidivism. In this project, 60,536 adult prison releases from the Oklahoma Department of Corrections between 1985 and 1999 were tracked until May 31, 2004. Recidivism was measured as a return to incarceration and cases were analyzed with a Cox Proportional Hazards Survival Regression, which allowed for the assessment of the relative hazards of returning to prison over time. Predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…These two studies and several others (see, e.g. Heil, Harrison, English, & Ahlmeyer, 2009;Huebner, Varano, & Bynum, 2007;Lattimore, MacDonald, Piquero, Linster, & Visher, 2004;Spivak & Damphousse 2006;Trulson, Marquart, Mullings, & Caeti, 2005;Trulson, 2007) lend support to arguments that misconduct predicts offending (Gendreau et al, 1997). French and Gendreau's (2006) metaanalysis of correctional programs found that interventions that reduced prison misconduct also reduced recidivism.…”
Section: Empirical Research On the Misconduct And Recidivism Relationmentioning
confidence: 66%
See 1 more Smart Citation
“…These two studies and several others (see, e.g. Heil, Harrison, English, & Ahlmeyer, 2009;Huebner, Varano, & Bynum, 2007;Lattimore, MacDonald, Piquero, Linster, & Visher, 2004;Spivak & Damphousse 2006;Trulson, Marquart, Mullings, & Caeti, 2005;Trulson, 2007) lend support to arguments that misconduct predicts offending (Gendreau et al, 1997). French and Gendreau's (2006) metaanalysis of correctional programs found that interventions that reduced prison misconduct also reduced recidivism.…”
Section: Empirical Research On the Misconduct And Recidivism Relationmentioning
confidence: 66%
“…9. One reviewer suggested examining the approach used by Spivak and Damphousse (2006). This approach consisted of creating a percentage of time served vs. assigned sentence length.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, although we are mindful of the body of work that suggests offenders do not specialize in types of offending (e.g., Piquero, Farrington, and Blumstein, 2007; cf. DeLisi et al, 2011; McGloin, Sullivan, Piquero, and Pratt, 2007), it is important to note that property offenders often are more likely to recidivate—independent of whether they were released early (Langan and Levin, 2002; Spivak and Damphousse, 2006; Wilson, 2005). Indeed, our findings from the community release sample analysis suggested that a prior theft or “other” nonviolent conviction increased the likelihood of recidivism.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on recidivism in Oklahoma, but none have focused on comparisons of private and public facilities (cf. Brewster & Sharp, 2002;Chown & Davis, 1986;Spivak & Damphousse, 2006). As we noted earlier, Oklahoma is an excellent location for a comparative evaluation of recidivism rates for public versus private prison inmates.…”
Section: Private Prisons and Recidivism In Oklahomamentioning
confidence: 99%
“…Lastly, the type of release also appears to be associated with inmates' postrelease performance. Spivak and Damphousse (2006) recently found that being paroled or released to probation, as opposed to being discharged without postrelease supervision, increased the hazard of recidivism, and being released to probation (via a split sentence) led to an especially high hazard of reincarceration. However, none of these studies examined the relationship between recidivism and having served in private versus public prisons.…”
Section: Predictors Of Recidivismmentioning
confidence: 99%